Decentralised model predictive control with stability constraints and its application in process control. (February 2015) - Tuan, H.D.; Savkin, A.; Nguyen, T.N.; Nguyen, H.T.
Abstract: This paper presents a novel decentralised model predictive control for a plant consisting of interconnected systems. A constructive technique for online stabilisation that is applicable to the model predictive controllers (MPC) is developed. The plant-wise stability is achievable by the newly introduced asymptotically positive realness constraint (APRC) for MPC. Simulations are provided to demonstrate the efficiency of the presented APRC.